PENGARUH MODEL PEMBELAJARAN INKUIRI PADA KOMPETENSI PERAWATAN KULIT WAJAH BERJERAWAT UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI SMK LABSCHOOL UNESA SURABAYA - aini, Nor Putri; Maspiyah, Maspiyah; Dwiyanti, Sri; Megasari, Dindy Sinta (Jurnal Tata Rias, 2025)
Education is a systematic effort to create an active, participatory, and meaningful learning process. This study has three main objectives, namely: (1) to determine the level of implementation of the inquiry learning model in learning activities; (2) to identify student learning outcomes after the model is implemented; and (3) to reveal student responses to the process of implementing the inquiry learning model on acne facial skin care competencies at SMK Labschool UNESA Surabaya. The type of research is One Group Pretest and Posttest Design. The subjects of the study were 34 students. Data were collected using observation methods in the form of the implementation of the learning process, tests in the form of cognitive tests and student response questionnaires. The results of the study obtained (1) the implementation of the inquiry learning model obtained an overall average of 3.85 categorized as very good, (2) hypothesis testing with a Sig. value (2-tailed) obtained 0.000 <0.05, so it is said that the inquiry learning model has a significant effect on increasing student learning outcomes and (3) student responses showed a mean of 94% in the very good category. Based on the research findings, it can be concluded that the application of the inquiry learning model has a positive effect on improving student learning outcomes. In addition, student responses to the competence of acne facial skin care are classified as very good, which shows that the inquiry model is able to create a more effective, interesting, and appropriate learning process for students' needs. Keywords: Inquiry Learning Model, Acne Facial Skin Care, Learning Outcomes